Reconstruction of the Electoral System to Improve the Control and Quality of Members of Parliament and Democracy in Indonesia - Arinaldo Adma; Margaretha Hanita (Jurnal Impresi Indonesia, 2025)
Elections are a crucial part of the political process that allows for the peaceful and orderly transfer of power. They involve interactions between prospective members of parliament, political parties, and voters who compete for representative mandates based on the interests and identity of each electoral district. However, in recent times, political contention has become increasingly divisive with candidates promoting identity rather than substantive ideas for improvement. Popularity and capital seem to be the driving forces behind the strategies of candidates heading to parliament. This noisy election process and the low quality of elected parliamentarians are accompanied by a weak accountability system, as there is no direct connection between voters and elected parliamentarians. This means that people from various social communities do not have a clear channel to put forward important issues in parliament. As a result, taking to the streets becomes a common medium for political expression. To improve the quality of people's representatives, politics, and democracy, the author suggests a combination of two models of democracy: representative and participatory. The combination would involve electing representatives as usual and selecting candidates proposed by community/group organizations (such as professional, religious, and other social communities) through internal organizational elections. This would ensure that the representatives truly represent the interests and identity of the people they serve.